Understanding Entrepreneurial Perception and Business Conditions in Vietnam Through the Approach of the Global Entrepreneurship Monitor - Huân, Lương Minh; Tuân, Nhâm Phong (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 30 No 2, 2014)
Abstract: Based on the survey results of 2,000 individuals and 36 national experts in 2013, and the analytical framework of the Global Entrepreneurship Monitor (GEM), this paper provides a broad view of the Vietnamese entrepreneurship characteristics in different phases; from intending to start, to just starting, to running a new or established business, and even to the discontinuance of a business. The paper also suggests an analytical framework condition for business development inVietnam. Key overall findings show that the perception of the existence of opportunities and business skills inVietnam is low. The intention of starting a business in the next three years is lower than the average ratio of 44.7 percent in other economies. The percentage of surveyed adults inVietnam who owned and managed business activities in the early stages has reached 15.4 percent, while the rate of start-up is only 4 percent, which is lower than the average rate in other economies. The rate of adults who abandoned their business activities in the past 12 months is 4.3 percent, including 2.5 percent of adults who discontinued their business and 1.8 percent of adults who sold their business for others to operate. Among the total of 12 business condition indicators inVietnam, the three following indicators have the highest levels: governmental regulations, the dynamics of the domestic market, and governmental policies. The three lowest ranking indicators encompass post-secondary education, secondary education, and business support services. Finally, this paper proposes recommendations for the improvement of business conditions and the promotion of the development of entrepreneurial activities inVietnam in the coming years. Keywords: GEM, entrepreneurship, business conditions.